EFFECT OF BRAND IMAGE IN INCREASING PURCHASE INTENTION OF BREAD MSMEs - Bunga Kartika; Nada Kusuma; Muh. Husriadi (Adisam Publisher, 2025)
Development The rapid growth of MSMEs bread in Kendari City is facing challenges in building a strong brand image to increase purchase intention in the midst of intense market competition and change preference consumers. This study aims to understand how brand image through utilization local cultural values and digital marketing strategies have effect so that intention buy consumers in MSMEs bread. Qualitative research method using design descriptive. Interview in-depth, observation participatory, and documentation and inductive data analysis through coding and categorization theme. The results of the study show that integration local cultural symbols in branding and strategic social media management own effect to increase trust and loyalty consumers. However, the risks of digital overexposure and limitations human resources are an obstacle in maintaining authenticity brand. Consistency of taste, social testimonials, and availability. product limited also plays an important role in strengthening purchase intention. The implications of this study emphasize importance digital marketing training that is oriented towards conservation cultural values and the development of adaptive marketing strategies to support the sustainability of bread MSMEs in the local market.